Smart computing and communication : first International Conference, SmartCom 2016, Shenzhen, China, December 17-19, 2016, Proceedings /: first International Conference, SmartCom 2016, Shenzhen, China, December 17-19, 2016, Proceedings. (2017) - Unknown
No abstract available